IDENTIFIKASI BAKTERI DAN FUNGI PADA AREA RHIZOSFER DI LINGKUNGAN TERCEMAR LOGAM KROM - Dwi Lestari Damayanti, - (2022)
The leather tanning industry in Sukaregang, Garut Regency is one of the biggest livelihoods for the locals community. The development of leather tanning industry has a negative impact if the waste product is not treated before being released into the environment. One of the wastes product from leather tanning that can pollute the environment is chromium metal. The method that can be used to overcome this environmental problem is by bioremediation using microorganisms such as bacteria and fungi. Bacteria and fungi isolated from chromium-contaminated soil usually have a higher resistance to survive in extreme conditions. The purpose of this study was to identify bacteria and fungi in plant rhizosphere area from chromium-contaminated environment and have a resistance to chromium metal. The rhizosphere soil samples were taken from plants around the waste collection tank in the Sukaregang area. The research methods include the isolation of microorganisms, macroscopic and microscopic morphological observations, biochemical activity tests of bacteria, and selection of chromium metal resistant microorganisms. The results showed that seven genus of bacteria were resistant to chromium metal, namely Bacillus, Enterobacter, Escherichia, Proteus, Pseudomonas, Serratia, and Staphylococcus, as well as six genus of fungi that were resistant to chromium metal, namely Aspergillus, Mucor, Neurospora, Paecilomyces, Rhizopus, and Saccharomyces.